The Concept of Person in Judaism, Christianity and Islam - Tamer, Georges (De Gruyter, 2023)
The sixth volume of the series "Key Concepts of Interreligious Discourses" investigates the roots of the concept of "person" in Judaism, Christianity and Islam and its relevance for the present time. The concept of "person" lies at the core of central ideas in the modern world, such as the value and development of personal identity, the sanctity of human person and the human rights based on that. In societies that are shaped by a long Christian tradition, these ideas are associated often with the belief in the creation of man in the image of God. But although Judaism shares with Christianity the same Biblical texts about the creation of man and also the Qur?an knows Adam as the first human being created by God and his representative on earth, the focus on the concept of "person" is in each one of these religions a different one. So, the crucial question is: how did the concept of "person" evolve in Judaism, Christianity and Islam out of the concept of "human being"? What are the special features of personhood in each one of these traditions? The volume presents the concept of "person" in its different aspects as anchored in Judaism, Christianity, and Islam. It unfolds commonalities and differences between the three monotheistic religions as well as the manifold discourses about the meaning of "person" within these three religions.
CRIS-Team Scopus Importer:2024-12-16